Sigmoid perforation due to baritoma - Lorenzelli, Juan A.; Garcia Pierce, Héctor (Cirugía del Uruguay, 1978)
The authors report on a case which is interesting because of its rare occurence, although it is advisable to be on the alert for its presence. Barium fecaloma which is retained for a long time in the recto-sigmoid will eventually be the cause of perforation due to decubitus ulcer as it rests on nonextensible surrounding tissues such as the pelvic wall Fecaloid peritonitis develops and rapidly kills the patinet. This case was favourably resolved by resection of a recto-sigmoid segment which included the barium fecaloma, closure of distal end and left iliac colostomy. Similar cases published in world literature are rare and this has lead its authors to publish this new case, the first to be known in this country.